Oppression and resistance : structure, agency, transformation - Musolf, Gil Richard, 1951- (Studies in symbolic interaction ;, 2017)
Oppression and resistance dialectically envelop everyday life, for both the privileged and the oppressed. The disenfranchised live under regimes in which repression ranges from brutal to institutionally subtle. The privileged socially reproduce their rule through ideology that justifies and policy that institutionalizes subjugation. However, rejecting depression, detachment, and disaffection that emerges from surviving ruling-class regimes, many previously dispirited, instead, choose defiance. They engage in subjectivity struggles by crafting critical consciousness, refusing to be dupes to ideology that represents them as inferior. They undertake social struggles demanding policy that dismantles institutional discrimination and that enhances opportunities for learning and achievement. The exploited, as best as they can in regimes of ruling class and white male supremacy, reconstruct their selves and, it is hoped, transform society. The qualitative studies that comprise this edited collection, present a structure-and-agency perspective, broadly defined, that constitutes the best sociological lens through which to understand oppression and resistance. Contributors interrogate various aspects of oppression and resistance, from the personal to the institutional, exploring situations in which the structure of oppression was insurmountable and illustrating cases in which agency was able to transform either individual or group identity.